The Genesis of Yi’an Style (易安體) in Medieval Chinese Poetry - Dashchenko, Hanna (Respectus Philologicus, 2022)
This article deals with the genesis of Yi’an style (易安體), the poetic style of the outstanding Chinese female poet of the Song dynasty Li Qingzhao (李清照, 1084–1155?). The empirical material for this research is her extant early 22 ci (1098–1108). The first part of the article briefly discusses the specific features of ci genre, which reached its heyday during the Song dynasty (宋朝, 960–1279). The second part examines the peculiar features of Li Qingzhao’s early ci, which indicate her pushing the limits of writing traditional Chinese poetry. These features are 1) modification of the classical themes and images; 2) introduction of love and erotic ci from a female perspective; 3) experiments with the composition of ci and their rhythmic and melodic structure. She introduced the lyric element into conventional ci, composing the poems with strong personal engagement. Her genre innovations lie in overcoming the limits and conventions of the genre, legitimating the Self of a poet in her distinctive personal style – Yi’an style.
Keywords: Li Qingzhao; ci genre; theme; images; feelings